Structural Model of Papuan Children’s Quality of Life in Different Ecosystem Zones in Papua - Stefanus P. Manongga; Serlie Littik (International Journal Labs, 2023)
The purpose of the study was to examine the situation of children's quality of life and assess the role of various related factors to the quality of life of children in various ecosystem zones in Papua Province. The study was conducted in four districts representing three ecosystem zones, namely the mainland coastal zone (Merauke and Sarmi Regencies), the middle plain zone (Nabire Regency) and the mountain zone (Jayawijaya Regency). This research was designed cross-sectionally, where the selection of the research site used a multistage sampling procedure with stratification and cluster techniques. Randomly involved 1481 sample households that had children under five for three zones. Data collection was carried out through structured interviews, observations and field measurements. To determine whether there are differences in related variables between ecosystem zones, the least significant different and Kruskal Wallis test is used. Testing and assessing the impact of malnutrition on child development, Structural Equation Modelling-Regression is used with a partial least square approach using the help of the SmartPLS application version 2.0. The results showed that the population of Papuan children with the risk of quality of life disorders (at risk) reached 50.57% and was the largest in the mountainous zone. Generally, they have impaired negative mood function, while children in the mountainous zone have impaired motor, autonomic, cognitive, social and negative mood functions.